Cross-linked cartilage acellular matrix film decreases postsurgical peritendinous adhesions - Park, Do Young; Yun, Hee Woong; Lim, Sumin; Truong, Minh Dung; Yin, Xiang Yun; Park, Jinho; Kim, Byeong Kook; Shin, Dong Il; Li, Xue Guang; Chung, Jun Young; Kim, Moon Suk; Min, Byoung Hyun (Artificial Organs, 2020)
Cartilage extracellular matrix contains antiadhesive and antiangiogenic molecules such as chondromodulin-1, thrombospondin-1, and endostatin. We have aimed to develop a cross-linked cartilage acellular matrix (CAM) barrier for peritendinous adhesion prevention. CAM film was fabricated using decellularized porcine cartilage tissue powder and chemical cross-linking. Biochemical analysis of the film showed retention of collagen and glycosaminoglycans after the fabrication process. Physical characterization of the film showed denser collagen microstructure, increased water contact angle, and higher tensile strength after cross-linking. The degradation time in vivo was 14 d after cross-linking. The film extract and film surface showed similar cell proliferation, while inhibiting cell migration and cell adhesion compared to standard media and culture plate, respectively. Application of the film after repair resulted in similar tendon healing and significantly less peritendinous adhesions in a rabbit Achilles tendon injury model compared to repair only group, demonstrated by histology, ultrasonography, and biomechanical testing. In conclusion, the current study developed a CAM film having biological properties of antiadhesion, together with biomechanical properties and degradation profile suitable for prevention of peritendinous adhesions.
Keywords: Acellular matrices; Anti-adhesive; Antiadhesion; Antiangiogenic; Cartilage extracellular matrixes; Cartilage matrix; Cross linking; matrix; Peritendinous adhesion; Thrombospondin 1; Animals; Cross-Linking Reagents; Extracellular Matrix; Glutaral; Human Umbilical Vein Endothelial Cells; Humans; Male; Mice; Rabbits; Swine; Tendon Injuries; Tissue Adhesions; Tissue Scaffolds; antiadhesion; cartilage matrix; peritendinous adhesion